👤

e) (2x + 5x2 - 4x - 5) + (2x + 1)​

Sagot :

Answer:

1. problem : [tex]\left(e\right)\left(2x\:+\:5x2\:-\:4x\:-\:5\right)\:+\:\left(2x\:+\:1\right)[/tex] =   [tex]e\left(5x^2-2x-5\right)+2x+1[/tex]

2. but if the problem is ; [tex]\left(2x\:+\:5x2\:-\:4x\:-\:5\right)\:+\:\left(2x\:+\:1\right)[/tex] =       [tex]5x^2-4[/tex]

Step-by-step explanation:

solution for the 1st prob;    [tex]=e\left(2x+5x^2-4x-5\right)+2x+1[/tex]

                           [tex]simplify: 2x+5x^2-4x-5: 5x^2-2x-5[/tex]

                           [tex]=e\left(5x^2-2x-5\right)+2x+1[/tex]

solution for he 2nd prob:

[tex]\left(2x+5x^2-4x-5\right)+\left(2x+1\right)[/tex] =[tex]2x+5x^2-4x-5+2x+1[/tex]

[tex]\mathrm{Group\:them:like\:terms}[/tex]

[tex]=5x^2+2x-4x+2x-5+1[/tex]

[tex]\mathrm{Add\:similar\:elements:}\:2x-4x+2x=0[/tex]

[tex]=5x^2-5+1[/tex]

[tex]\mathrm{Add\:the\:numbers:}\:-5+1=-4\\[/tex]

then the answer will be:   [tex]=5x^2-4[/tex]